2020
DOI: 10.20944/preprints202009.0009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Double Dose Dapsone Combination Therapy in the Treatment of Chronic Lyme Disease/Post-Treatment Lyme Disease Syndrome (PTLDS) and Associated Co-infections: A Report of Three Cases

Abstract: Three patients with multi-year histories of relapsing and remitting Lyme disease and associated co-infections despite extended antibiotic therapy were each given double dose dapsone combination therapy (DDD CT) for a total of 7-8 weeks. At the completion of therapy, all three patients major Lyme symptoms remained in remission for a period of 25-30 months. In conclusion, Double dose dapsone therapy could represent a novel and effective anti-infective strategy in chronic Lyme disease/PTLDS, especially in those i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Pothineni et al published that disulfiram, a Federal Drug Administration (FDA)repurposed medication, can inhibit Borrelia in culture [120], while Liegner et al demonstrated that both low-and especially high-dose disulfiram regimens were able to put some chronically ill Lyme patients into long-term clinical remission [114,115]. From 2016 to 2023, Horowitz et al published eight studies on the efficacy of dapsone, another FDAapproved repurposed medication, where dapsone was shown to be effective in culture against the biofilm/stationary forms of Borrelia burgdorferi [75] and where over 375 patients had statistical improvement in their Lyme disease and tick-borne symptoms using dapsone combination therapy and the precision medicine MSIDS model [14,30,38,39,[71][72][73]. An evidence-based definition by the ILADS Working Group in 2019 further clarified the term 'chronic Lyme disease' (CLD), providing a literature review that validated the role of persistent Borrelia burgdorferi sensu lato (Bbsl) infections in chronic disease [135].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pothineni et al published that disulfiram, a Federal Drug Administration (FDA)repurposed medication, can inhibit Borrelia in culture [120], while Liegner et al demonstrated that both low-and especially high-dose disulfiram regimens were able to put some chronically ill Lyme patients into long-term clinical remission [114,115]. From 2016 to 2023, Horowitz et al published eight studies on the efficacy of dapsone, another FDAapproved repurposed medication, where dapsone was shown to be effective in culture against the biofilm/stationary forms of Borrelia burgdorferi [75] and where over 375 patients had statistical improvement in their Lyme disease and tick-borne symptoms using dapsone combination therapy and the precision medicine MSIDS model [14,30,38,39,[71][72][73]. An evidence-based definition by the ILADS Working Group in 2019 further clarified the term 'chronic Lyme disease' (CLD), providing a literature review that validated the role of persistent Borrelia burgdorferi sensu lato (Bbsl) infections in chronic disease [135].…”
Section: Discussionmentioning
confidence: 99%
“…Recent scientific studies have strongly suggested that pulsed biofilm and persister drug regimens, such as dapsone combination therapy, may be an effective solution for the management of CLD/PTLDS, along with the treatment of polymicrobial infections and multiple inflammatory triggers [14,30,38,39,[71][72][73]. Emerging research indicates that biofilms are likely part of many, and probably most, chronic infections, providing a protected niche for pathogenic bacteria to survive, contributing to the burden of inflammation [74].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PZA has been published to help shorten the course of mycobacterium therapy by demonstrating efficacy in latent infections, phenotypic resistance, or tolerance [241]. A case study on CLD and Bartonella published several years ago in a patient with Behçet's disease, a severe autoimmune illness, demonstrated that dapsone combination therapy along with PZA had efficacy against a stealth infection with Bartonella, helping to relieve resistant symptoms [105]. It was therefore chosen as the fifth medication in this cohort of patients (84%) who were chronically ill and exposed to multiple species of Bartonella.…”
Section: Discussionmentioning
confidence: 99%
“…In five separate clinical studies involving more than 365 patients, dapsone combination therapy led to statistically verified improvement in relieving eight major Lyme symptoms in our patients, including sweats/chills, fatigue, joint, muscle, and/or nerve pain, headaches, insomnia, and cognition [50,51,[102][103][104]. In a 6th clinical case study involving chronic LD and Behçet's disease (a severe multisystemic autoimmune illness), a patient who had been ill for 20 years reported significant symptom improvement when pyrazinamide (PZA) was added to dapsone combination therapy (DDSCT) despite a history of failing multiple disease-modifying antirheumatic drugs (DMARDS) [105]. Bartonella titers turned positive in this patient after adding pyrazinamide (PZA) to other intracellular antibiotics (minocycline, rifampin, and dapsone), where Behçet's ulcers and granulomatous skin changes resolved for the first time in decades, implicating a potential role for Bartonella in the autoimmune manifestations of Behçet's [105].…”
Section: Introductionmentioning
confidence: 99%